Estudo computacional do impacto ambiental de emissões do processo Kraft na qualidade do ar - Melo, Joelma Ribeiro (2014)
The Kraft pulp production is associated with the emission of harmful air pollutants that can have impact in the environment, on property and on human health. The air quality is directly influenced by the distribution and intensity of emissions and verifying the levels of pollutants in the atmosphere can be performed by monitoring the pollutants. However most Brazilian cities do not present air quality monitoring networks and those that have air quality monitoring are the state?s capitals. In the absence of pollutants monitoring and unavailability of data of pollutants concentrations, it is possible to estimate them by means of mathematical models which simulate the transport of pollutants into the atmosphere. The aim of this study was to quantify and evaluate air pollutants dispersion, using Aermod atmospheric model, by simulating the dispersion of pollutants: particular matter (PM), total reduced sulphur (TRS), sulphur oxides (SOx), nitrogen oxides (NOx) and carbon monoxide (CO), emitted from eight stationary sources of the Kraft process for pulp production. The methodology applied for the simulation experiments consists of: delineation and characterization of the study area; operational and physical characterization of emission sources; obtaining topographical features of the region. Meteorological parameters that characterize the climate conditions of the region, also necessary form simulations, were obtained by meteorological model MM5. The simulations showed the city center located in southwest of the study region, having predominant wind flows, was affected by the pollutant plume. However the most impacted areas were at the northwest and the southeast of the emission sources for the majority of cases. The highest annual averages concentrations were nearby industry, at the southeast region, in relation to the emission sources. For hourly and daily averages concentrations, the highest values occur near the emission sources in locals where the topographic coordinates were elevated. Peak concentrations estimated by the model for hourly, daily and annual averages were respectively: 55.69 ?g/m³, 12.74 ?g/m³ and 2.06 ?g/m³ for PM; 2.59 ?g/m³, 0.27 ?g/m³ and 0.06 ?g/m³ for TRS; 3.45 ?g/m³, 0.47 ?g/m³ and 0.09 ?g/m³ for SOx; 189.36 ?g/m³, 34.88 ?g/m³ and 5.83 ?g/m³ for NOx; and 30.44 ?g/m³, 13.26 ?g/m³ (8 h), 5.63 ?g/m³ and 0.96 ?g/m³ for CO. Maximum concentrations estimated by the model for the pollutants were below the concentrations limits established by Conama Resolution 003/1990 and by USEPA standards for TRS pollutant. The observed concentrations of total suspended particulate matter (TSP) and particular matter (PM10) were represented fairly well, verifying a slightly underestimation of predicted values in comparison to those observed in air monitoring station. Therefore, the dispersion model can be used in a qualitative manner to indicate adequate local to measure the concentration of pollutants in an air quality monitoring network. It was found from literature that the maximum concentrations estimated for pollutants in the study area are below a significant value that could have harmful effect on human health.